GREEN INNOVATION AND GREEN COMPETITIVE ADVANTAGE MEDIATE THE INFLUENCE OF GREEN MARKETING ORIENTATION ON GREEN MARKETING PERFORMANCE IN SME INDONESIA - Putri, Viajeng Purnama; Riyanto, Dicky Wisnu Usdek (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This study aims to analyze the relationship between green innovation and green competitive advantage mediating the influence of environmentally friendly marketing orientation on the performance of environmentally friendly marketing using the SEM-PLS analysis tool in Indonesian MSMEs. The results of this study Green Innovation (GI) has a significant effect on Environmental Marketing Performance (EMP). Green Marketing Orientation (MO) has a significant effect on Environmental Marketing Performance (EMP). Green Marketing Orientation (MO) has a significant effect on Green Competitive Advantage (GCA). Green Marketing Orientation (MO) has a significant effect on Green Innovation (GI). Green Marketing Orientation (MO) has a significant effect on Environmental Marketing Performance (EMP) through on Green Competitive Advantage (GCA). Green Marketing Orientation (MO) has a significant effect on Environmental Marketing Performance (EMP) through Green Innovation (GI).